A longitudinal study of the process of acquiring absolute pitch: A practical report of training with the 'chord identification method'. (January 2014) - Sakakibara, Ayako
The purpose of this study was to investigate longitudinally the process of acquiring absolute pitch (AP). Twenty-four young children (aged 2 to 6 years) without AP were trained to acquire AP using Eguchi's (1991) Chord Identification Method (CIM). All children were able to acquire AP (except two who ceased training). Results suggest that, at a minimum, children younger than 6 years old are capable of acquiring AP through intentional training. Furthermore, children's errors observed during training suggested the transition of different strategies relying respectively on tone height and tone chroma. Initially, children identified chords using a strategy depending primarily on tone height, then gradually they began to attend to tone chroma to identify chords and this process ultimately led to acquisition of AP.